2023
DOI: 10.1039/d3an00551h
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent probe for lipid droplet polarity imaging with low viscosity crosstalk

Abstract: Monitoring the variations of lipid droplets (LDs) polarity is of great significance for the investigation of LDs-related cellular metabolism and function. We hereby report a lipophilic fluorescent probe (BTHO) with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Then, we studied the fluorescence intensity changes due to drug induced changes in polarity. It has been reported that H 2 O 2 can increase the polarity of lipid droplets, while LPS can decrease the polarity of lipid droplets, 59,60 so we chose H 2 O 2 and LPS as drugs to induce the polarity changes of intracellular lipid droplets. The cells induced by H 2 O 2 increased the polarity of lipid droplets, which led to the increase of fluorescence intensity, and the cells induced by LPS reduced the polarity of lipid droplets, which led to the decrease of fluorescence intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we studied the fluorescence intensity changes due to drug induced changes in polarity. It has been reported that H 2 O 2 can increase the polarity of lipid droplets, while LPS can decrease the polarity of lipid droplets, 59,60 so we chose H 2 O 2 and LPS as drugs to induce the polarity changes of intracellular lipid droplets. The cells induced by H 2 O 2 increased the polarity of lipid droplets, which led to the increase of fluorescence intensity, and the cells induced by LPS reduced the polarity of lipid droplets, which led to the decrease of fluorescence intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a few fluorescent probes based on the D–A structure have been developed for the polarity detection of intracellular LDs [ 44 , 45 , 46 , 47 ]. For instance, Lin et al [ 44 ] reported a D–A molecule with ICT properties, CTPA, which was sensitive to polarity and specifically targeted LDs.…”
Section: Introductionmentioning
confidence: 99%
“…), 9 which may have an abnormal impact on the cellular microenvironment. 10 The structural similarity between adamantane (Ad) and the hydrophobic cavity of β-CDs enables the formation of host-guest complexes with a binding constant in the range of 10 3 -10 4 M −1 at a 1 : 1 stoichiometry, which greatly improves the thorny problem of excessive β-CD dosage. 11,12 Benzo[a]phenoxazine probes exhibit near-infrared emission and excellent biocompatibility, [13][14][15] but their low fluorescence quantum yields in aqueous solution hinders their application in aqueous systems and biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…), 9 which may have an abnormal impact on the cellular microenvironment. 10 The structural similarity between adamantane (Ad) and the hydrophobic cavity of β-CDs enables the formation of host–guest complexes with a binding constant in the range of 10 3 –10 4 M −1 at a 1 : 1 stoichiometry, which greatly improves the thorny problem of excessive β-CD dosage. 11,12…”
Section: Introductionmentioning
confidence: 99%